The Language of the Official Letters of Kazakh Khan Abu'l-hayır to the Russians - Umit Kydyrbayeva; Nazym Shuinshina Meta (Türkiyat Mecmuası)
Written works are critical for researching a country’s past history, language, moral values, and social status. The official letters written during the Khanate dynasty of the 17th-19th centuries are one set of manuscripts that have made significant contributions to the history of the Kazakh people. The content of the Kazakh Khans’ official letters also differ. Since 1732, original copies of the letters the Kazakh Khans and sultans sent to neighboring state administrators and representatives have been preserved in the rare works section of Kazakhstan and Russia’s archives, with the majority of these letters taking the form of submissions, petitions, and declarations. This article examines the language characteristics of the official letters sent by the Lesser Zhuz Han Ebü'l-hayr to the Russian queen and Russian tsardom representatives in Kazakh lands. The article compares the similarities and differences with today’s Kazakh language by focusing on the language features and explaining them distinctly. Furthermore, the article mentions some features that were determined with regard to spelling, phonology, vocabulary, and morphology. As a result, the purpose of this research article has been to investigate the historical development of the Kazakh language in the 18th century with the goal of identifying the language features found in official correspondence from the 19th century.